Amplifying Outcomes by Addressing Inequality: The Role of Gender-transformative Approaches in Agricultural Research for Development. (November 2015) - Kantor, Paula; Morgan, Miranda; Choudhury, Afrina
Increasing agreement on the relevance of gender and social equalities to agricultural development outcomes has not come with the same consensus within the development community regarding ways to intervene in the sector to foster equality. The guiding principles of agriculture research for development (AR4D) and its focus on capacity development can contribute to this debate and to advancing gender integration in the sector if the "social threads" within its principles are developed more thoroughly. The aim of the article is to articulate how the social dimension of AR4D could be further developed through the conceptualization and operationalization of gender-transformative approaches (GTAs). The article provides a case study from the aquaculture sector of Bangladesh to illustrate why this is needed, and it describes some ways forward to move GTAs into agricultural practice and test their contributions to development outcomes. Such an action research agenda will generate learning that can be used to make the most out of synergies between enhanced social equality and capacities to innovate.